anonymous
  • anonymous
Generate the first 5 terms of this sequence: f(1) = 2 and f(2) = 3, f(n) = f(n - 1) + f(n - 2), for n > 2. 2, 3, 5, 7, 9 2, 3, 4, 7, 11 2, 3, 5, 9, 11 2, 3, 5, 8, 13
Mathematics
  • Stacey Warren - Expert brainly.com
Hey! We 've verified this expert answer for you, click below to unlock the details :)
SOLVED
At vero eos et accusamus et iusto odio dignissimos ducimus qui blanditiis praesentium voluptatum deleniti atque corrupti quos dolores et quas molestias excepturi sint occaecati cupiditate non provident, similique sunt in culpa qui officia deserunt mollitia animi, id est laborum et dolorum fuga. Et harum quidem rerum facilis est et expedita distinctio. Nam libero tempore, cum soluta nobis est eligendi optio cumque nihil impedit quo minus id quod maxime placeat facere possimus, omnis voluptas assumenda est, omnis dolor repellendus. Itaque earum rerum hic tenetur a sapiente delectus, ut aut reiciendis voluptatibus maiores alias consequatur aut perferendis doloribus asperiores repellat.
chestercat
  • chestercat
I got my questions answered at brainly.com in under 10 minutes. Go to brainly.com now for free help!
amoodarya
  • amoodarya
f(3)=f(2)+f(1)=2+3=5 f(4)=f(3)+f(2)=5+3=8 f(5)=f(4)+f(3)=8+5=13 can you go on ?
anonymous
  • anonymous
i dont even know how you got that
amoodarya
  • amoodarya
it is easier to say : every number in this sequence = sum of two term before

Looking for something else?

Not the answer you are looking for? Search for more explanations.

More answers

anonymous
  • anonymous
oh ok. thank you
anonymous
  • anonymous
so the last one?
amoodarya
  • amoodarya
let's do it again : put n=3 in relation f(3)=f(3-1)+f(3-2) --->f(3)=f(2)+f(1) now put f(2) ,f(1)
anonymous
  • anonymous
oh ok. makes more sense now
amoodarya
  • amoodarya
now , can you tell me the next number is ?

Looking for something else?

Not the answer you are looking for? Search for more explanations.